DEVELOPING LEARNING MATERIALS WITH SEARCH-SOLVE-CREATE-SHARE STRATEGY TO ENCHANCE PRE-SERVICE TEACHERSâ BASIC SKILLS OF TEACHING MATHEMATICS - Rahayu, Diar Veni; Kusumah, Yaya S.; Darhim, Darhim (EDU-MAT, 2017)
One of skills which must be achieved by mathematics pre-service teachers is the basic skills of teaching mathematics. By having these skills, the pre-service teachers are expected to be able to become qualified teachers of the field they are going to have. However, there are still many mathematics pre-service teachers and mathematics teachers who havenât achieved good basic skills of teaching mathematics. This was one of many factors that cause studentsâ low achievement in math. This study aims at solving the problem by developing learning materials with Search-Solve-Create-Share strategy to enhance the pre-service teachersâ basic skills of teaching mathematics. The research method used in this study is modified research and development method. In a nutshell, this study provides a significant contribution towards research in the mathematics education field particularly in producing suitable learning materials to enhance the pre-service teachersâ basic skills of teaching mathematics.Â Keywords: Basic Skills of Teaching Mathematics, Learning Material, Search-Solve-Create-Share